Observational database study on preeclampsia and postpartum medical care up to 7.5 years after birth - Scholz, Anna; Haßdenteufel, Kathrin; Gutsfeld, Raphael; Müller, Mitho; Götz, Maren; Bauer, Armin; Wallwiener, Markus; Brucker, Sara Y.; Joos, Stefanie; Colombo, Miriam Giovanna; Hawighorst‑Knapstein, Sabine; Chaudhuri, Ariane; et al. (Scientific reports, 2022)
Preeclampsia is associated with a substantially increased long-term risk for cardiovascular, cerebrovascular and renal disease. It remains unclear whether and to which extent specialized medical postpartum care is sought. We aimed to assess current utilization of postpartum primary and specialized care and medication prescription behavior in women who experienced preeclampsia. This retrospective observational study based on statutory claims data included 193,205 women with 258,344 singleton live births between 2010 and 2017 in Southern Germany. Postpartum care was evaluated by analyzing and comparing the frequency of medical consultations in primary and specialized care and prescriptions for antihypertensive medication among women with and without preeclampsia up to 7.5 years after delivery. Gynecologists and general practitioners were the main health care providers for all women. Although specialized postpartum care was sought by more women after preeclampsia, the effect size indices revealed no considerable association between a history of preeclampsia and the utilization of specialized outpatient aftercare (e.g. 2% vs. 0.6% of patients with and without preeclampsia who consulted a nephrologist during the first year postpartum, r = 0.042). Preeclampsia was associated with an increased risk to take any antihypertensive medication after delivery (HR 2.7 [2.6; 2.8]). Postpartum referral to specialized outpatient care and quarterly prescriptions of antihypertensives following preeclampsia failed to match the early and rapidly increased incidence and risk of hypertension. These data highlight the missed opportunity to implement a reasonable follow-up strategy and prevention management in order to achieve long-term clinical benefits.
Gesehen am 05.07.2023